2022
DOI: 10.3389/fendo.2022.1037211
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease is specifically related to the risk of hepatocellular cancer but not extrahepatic malignancies

Abstract: ObjectiveWe performed a matched cohort study among individuals with and without nonalcoholic fatty liver disease (NAFLD) to determine: 1) the incidence of cancers (extrahepatic and liver) and their spectrum and 2) if NAFLD increases the risk of extrahepatic cancers.MethodsThe NAFLD and non-NAFLD (control) cohorts were identified from electronic medical records via International Classification of Diseases (ICD) codes from a single center and followed from 2010 to 2019. Cohorts were matched 1:2 for age, sex, rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Among participants in the UK Biobank (2006–2019), individuals at high risk for MASLD had a 1.23‐fold increased risk of non‐liver gastrointestinal cancers compared with individuals at low risk for MASLD 3 . In contrast, a smaller matched cohort study from a single US center (1412 subjects, 34% with MASLD) did not show an increased risk for EHC after matching major risk factors including age, sex, race, BMI, and diabetes status 4 . As MASLD is a multisystem disorder, it remains difficult to investigate its contribution to EHC independently of obesity and metabolic dysfunction 12 …”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Among participants in the UK Biobank (2006–2019), individuals at high risk for MASLD had a 1.23‐fold increased risk of non‐liver gastrointestinal cancers compared with individuals at low risk for MASLD 3 . In contrast, a smaller matched cohort study from a single US center (1412 subjects, 34% with MASLD) did not show an increased risk for EHC after matching major risk factors including age, sex, race, BMI, and diabetes status 4 . As MASLD is a multisystem disorder, it remains difficult to investigate its contribution to EHC independently of obesity and metabolic dysfunction 12 …”
Section: Discussionmentioning
confidence: 88%
“…3 In contrast, a smaller matched cohort study from a single US center (1412 subjects, 34% with MASLD) did not show an increased risk for EHC after matching major risk factors including age, sex, race, BMI, and diabetes status. 4 As MASLD is a multisystem disorder, it remains difficult to investigate its contribution to EHC independently of obesity and metabolic dysfunction. 12 In our study, the ASI of cancer (all cancers) was not influenced by the presence of T2D at index admission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the risk of progressive liver disease, the leading causes of death for people with NAFLD are cardiovascular disease and extrahepatic malignancy. Several 18 but not all 19 studies have reported risks of major adverse cardiovascular events and extrahepatic cancers, particularly colorectal cancer, in people with NAFLD, but these associations may be confounded by shared metabolic dysfunction related to obesity and diabetes mellitus driving systemic inflammation and changes in the gut microbiota and secondary bile acid levels 20 . Nevertheless, our finding of relationships between several medical conditions and the risk of NAFLD progression to decompensation indicates the multisystem nature of metabolic dysregulation and the need for a holistic approach to management.…”
Section: Discussionmentioning
confidence: 99%
“…It involves a spectrum of diseases, including hepatic steatosis and non-alcoholic steatohepatitis (NASH) (2). NAFLD may lead to lifethreatening hepatic diseases, such as liver cirrhosis and hepatocellular carcinoma (HCC), and extrahepatic diseases, such as cardiovascular disease and dementia (3)(4)(5)(6). Along with advances in retrospective operational definitions, such as fatty liver index and Korea National Health and Nutrition Examination Survey-NAFLD score, and non-invasive diagnostic approaches for NAFLD, prevention, management, and treatment of NAFLD are being actively investigated (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%